Peluang Pengembangan Pariwisata Halal Melalui Optimalisasi Wakaf di Daerah Istimewa Yogyakarta - Irawan Agung Wibowo; Nur Fatwa (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The development of the Islamic economy is not limited to the Islamic banking sector, but also encompasses other growing aspects, such as halal tourism. Halal tourism is a tourism segment that adheres to the principles of Islamic Sharia, including aspects of food, accommodation, entertainment, and other services. This phenomenon reflects significant growth in global awareness of Islamic culture, values, and ethics. The development of the concept of halal tourism in the Special Region of Yogyakarta reflects a commitment to maintaining and enhancing tourism appeal, with a focus on services in line with Sharia principles. Various tourist attractions in this region have been upgraded towards the concept of halal tourism, taking into consideration the needs of Muslim travelers. However, further efforts in innovation and development are still required to ensure a quality tourism experience. This paper aims to delve deeper into the potential of tourism to be developed into halal tourism in the Special Region of Yogyakarta, and optimization strategy of halal tourism development based on waqf and its benefits. This writing method employs a qualitative approach with literature review and observation. This is to facilitate researchers in obtaining accurate data in the field.